3D Macroporous MoxC@N‐C with Incorporated Mo Vacancies as Anodes for High‐Performance Lithium‐Ion Batteries. Issue 8 (26th April 2018) - Liu, Shenghong; Li, Feng; Wang, Dan; Huang, Chunmao; Zhao, Yanming; Baek, Jong‐Beom; Xu, Jiantie
Abstract: High electronic conductivity, low average working voltage, and high theoretical capacities enable molybdenum carbide‐based materials as promising anodes for lithium‐ion batteries (LIBs). Apart from the increase in the number of additional active sites, further enhancement in the specific activity of the active sites is also an effective way to improve the electrochemical performance of the molybdenum carbide‐based electrodes. Here, a series of 3D cross‐linked macroporous Mo x C@N‐C nanocrystals with rich incorporated Mo vacancies, high specific activity of active sites, and nitrogen‐doped carbon (N‐C) coating are designed and synthesized using a simple method. Benefitting from its 3D robust structures for the rapid transporting and additional storage of Li +, the Mo x C@N‐C‐2.5 displays a high initial reversible capacity of 879.3 mAh g −1 at 0.05 A g −1 . Moreover, the Mo x C@N‐C‐2.5 shows a high discharge capacity of 825.3 mAh g −1 at 0.5 A g −1 with an initial capacity retention of 61.9% after 200 cycles. As expected, this facile strategy can be extended to the fabrication of other nanocomposites with rich defects, numerous porous structures, and heteroatoms doped carbon coating as electrodes toward high‐performance LIBs. Abstract : A series of Mo x C@N‐C nanocrystals with rich incorporated Mo vacancies, high specific activity of active sites, 3D cross‐linked macroporous nanostructure, and nitrogen‐doped carbon coating are designed and synthesized. Benefitting from the unique robust and high activity structures, the Mo x C@N‐C as anodes for lithium‐ion batteries display outstanding lithium storage properties.